Sistemas petrolíferos do Meso-Cenozóico e sua relação com os evaporitos como rochas selantes: o exemplo da Bacia Lusitana - RAMOS, Nazareth Christina Pontes (2019)
Studying the petroleum reservoirs is based on a steady analysis of characteristics and properties of rocks such as: porosity, permeability and the seal-rock. Porosity degree and type and also its permeability are components that help to define a reservoir-rock. However, oil only can be explored if there is a seal-rock in its role to avoid the oil migration until the surface. Oil geologists gave the name of trap to an association of seal and reservoir rocks. The oil only can be recovered if there is a trap. It must have a reservoir-rock with porosity and permeability capable of oil circulation and accumulation, although enveloped by a seal-rock. The aim of this work is to study the evaporites as seal-rocks and why they can understood and identified as a typical seal-rock of Meso-Cenozoic to analyze its relationships with formation of oil prone rocks and oil generation could lead to a successful oil prospecting petroleum program.